Language Features of Author's Styles: A Comparison of the Work of Two Authors (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the language features of the author's styles, their uniqueness, the importance of comparing the works of two authors are highlighted, and it is considered very relevant in the fields of culture, language, literature, art, science.